Evaluation of Petty Cash Accounting: A Case Study at a Job Training Institution - Villania Putri, Destian; Era Yusdita, Elana (KnE Social Sciences, 2024)
This research aims to evaluate the petty cash recording process at the SCK job training institution. Researchers used qualitative methods, namely interviews, observation, and analysis of the petty cash accounting system. The implementation of petty cash has been carried out by procedures and the recording has been carried out according to the flow established by the institution. However, several things are inaccurate and not by the accounting information system that should be implemented by petty cash users using the imprest fund method. In order not to experience a shortage of petty cash funds, companies should use an imprest system that meets standards. Companies must pay attention to the principles of internal control so that the institution’s operational activities run according to the expected goals and avoid misappropriation of petty cash funds. Keywords: Petty cash recording, imprest fund system, accounting system information